Characterisation of Escherichia coli from smoked "etak" (Corbicula fluminea) - Nur Eastiharah Mohamad Hairin (2011)
Corbicula fluminea (C. fluminea) also known as Asian Clam lives in freshwater. It is called "etak" as its common name in Kelantan. Smoked "etak" is a popular dish among the local which is processed or smoked by heat. "Etak" is a filter feeder and capable to accumulate bacteria and heavy metals from polluted river or water stream. The objectives of this study are to isolate and identify Escherichia coil (E. col') in smoked "etak", investigate antibiogram and characterise heavy metal profile of E. coll. The methodology in this study involves sampling collection of smoked "etak", isolation and identification of E. coil in flesh and shell by using Commercial Kit, antibiotic susceptibility test by Kirby Bauer Disk Diffusion method and heavy metal test by agar dilution method. The results showed E. coil isolates from smoked "etak" were found highly sensitive to Nalixidic Acid, Amoxycillin, and Oxolinic Acid. In terms of heavy metal resistance patterns, E. coil isolates were resistant to Chromium, Mercury and Zinc. Overall, E. coli in smoked "etak" has potential to develop antibiotic and heavy metal resistant which can be harm to human health.